2020
DOI: 10.1002/cam4.2942
|View full text |Cite
|
Sign up to set email alerts
|

An immune relevant signature for predicting prognoses and immunotherapeutic responses in patients with muscle‐invasive bladder cancer (MIBC)

Abstract: Immune checkpoint inhibitors (ICIs) are novel treatments that significantly improve the survival time of MIBC patients, but immunotherapeutic responses are different among MIBC patients. Therefore, it is urgent to find predictive biomarkers that can accurately identify MIBC patients who are sensitive to ICIs. In this study, we computed the relative abundances of 24 immune cells based on the expression profiles of MIBC patients using single-sample gene set enrichment analysis (ssGSEA).Unsupervised clustering an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 59 publications
3
51
0
Order By: Relevance
“…A recent study 13 has constructed a ceRNA network, which was of high prognostic value, to achieve a deeper comprehension to the RNA regulatory network in BLCA. Besides, although several immune-relevant signature [34][35][36] have been constructed to predict the survival of BLCA, few studies concentrated on immune-relevant genes revealing the prognosis based on ceRNA hypothesis. In this study, we integrated the TCGA-BLCA database and GEO database to determine an immune-related risk signature and constructed an immune-relevant ceRNA network including 5 mRNAs, 24 miRNAs and 86 lncRNAs, leading to a better understanding of the oncological immunology of BLCA from the angle of RNA interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study 13 has constructed a ceRNA network, which was of high prognostic value, to achieve a deeper comprehension to the RNA regulatory network in BLCA. Besides, although several immune-relevant signature [34][35][36] have been constructed to predict the survival of BLCA, few studies concentrated on immune-relevant genes revealing the prognosis based on ceRNA hypothesis. In this study, we integrated the TCGA-BLCA database and GEO database to determine an immune-related risk signature and constructed an immune-relevant ceRNA network including 5 mRNAs, 24 miRNAs and 86 lncRNAs, leading to a better understanding of the oncological immunology of BLCA from the angle of RNA interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing ssGSEA strategy, which has been proved to be effective for tumor grouping based on immune in ltrating status in multiple studies 17,35,37 , 411 BLCA patients were labeled with high-immunein ltrating and low-immune-in ltrating, and then genomic difference detection was performed to achieve the latent immune-relevant lncRNA, mRNA and miRNA. To identify the genes correlated with tumorigenesis of BLCA, we compared the genomic expression difference between the parcancerous tissues and malignant bladder tissues by "edgeR" package of R. WGCNA was implemented to obtain the lncRNAs mostly relevant to the process of immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies demonstrated that immune-related lncRNAs have a unique value in the prognosis of several cancers. The heterogeneous expression of lncRNAs was identi ed among different immune-in ltrating groups in muscle-invasive bladder cancer [10]. The potential value of immune-related lncRNAs as prognostic indicators has been validated in several cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al developed a seven-gene signature related with epithelial-mesenchymal transition (EMT) process, which could stratify patients into different risk groups with distinct prognosis[17]. Jiang et al analyzed genes associated with immune cells infiltration in MIBC and developed a nine-gene signature which could distinguish patients with different prognoses and immunotherapeutic response[18]. However, genetic biomarkers associated with cancer stemness features were seldom studied in bladder cancer.In the present study, we developed and validated a novel stemness-related seven-gene signature for predicting prognosis and treatment response in MIBC patients, which is different from previously reported gene signatures.…”
mentioning
confidence: 99%